Stony heart country - Metzenthen, David, 1958- (Ringwood, Victoria : Penguin Group Australia, 1999)
'You see, out here in the country,' Bernie Tolliver tells Aaron Knott, 'things are complicated.' Dangerously complicated, Aaron discovers - and that's before he's met Rose, the haunted young woman wandering the wild paddocks. Aaron's father is a city consultant brought in to sack country workers. Aaron Knott is the city kid taken along for the ride. And the ride in the Rocky Rises is always rough.
Imprint: e-penguin.
For young adults.
Keywords: Country life -- Australia -- Fiction; Country life -- United States -- Juvenile fiction; High schools -- Fiction; Interpersonal relations -- Fiction; Moving, Household -- Fiction; Schools -- Fiction; Country life; General fiction (Children's / Teenage); General fiction (Children's / Teenage); Personal & social issues: family issues (Children's / Teenage); Personal & social issues: family issues (Children's / Teenage); Romance & relationships stories (Children's / Teenage); Romance & relationships stories (Children's / Teenage); Thrillers (Children's / Teenage); Thrillers (Children's / Teenage); Australia -- Fiction; United States; Australian; Electronic books; Fiction